Peran Manajer Dalam Meningkatkan Kinerja Keuangan Bank OCBC Tbk - Yulfiswandi; Candy; Alzi; Miftachul Choiri; Brahmantya Chriswardhana; Jimmy Tjong (Jurnal Manajemen, 2024)
The aim of the research was to observe and analyze the role of managers in banking financial reports. The research method uses a quantitative descriptive research model with PT. Bank Oversea-Chinese Banking Corporation NISP or PT. Bank OCBC NISP Tbk. as a research object. The sample is the financial report of PT. Bank OCBC NISP Tbk. from 2018 to 2022. The research results concluded that PT. Bank OCBC NISP Tbk. included in the category of "healthy" banking companies assessed by ROA, ROE and NIM, but BOPO is considered "unhealthy". The research recommendation is that directors and managers must increase operational monitoring and operational expenses incurred to run operational businesses to reduce the BOPO ratio in order to achieve "healthy" standards in accordance with the standards of the Indonesian Banking Statistics Agency.